Endogenous GHB concentrations in whole blood postmortem samples as a biomarker for post mortem interval estimation – A set of real cases analysis - Castro, André Lobo (2016)
Gamma-hydroxybutyric acid (GHB) is an endogenous compound which has a story of clinical use and illicit abuse since the 1960’s. Its postmortem behaviour, namely regarding degradation and metabolism, has been increasingly studied to be used as a putative biomarker for post-mortem interval (PMI) estimation. Thus, whole blood post-mortem GHB levels were obtained in thirty two real cases with previous information on death and autopsy data. The samples were treated through sample methanolic precipitation followed by GC-MS/MS analysis (LLOQ=0.1 mg/L). No differences were encountered for the other parameters evaluated, including age [under 44 years-old - 7.87  2.06 mg GHB/L (n=7), 45 to 60 years-old - 6.80  3.67 mg GHB/L (n=13) and over 61 years-old - 5.72  2.39 mg GHB/L (n=12), p0.05], gender [men - 7.79  5.04 mg GHB/L (n=23), women - 6.72  2.60 mg GHB/L (n=9), p=0.273], cause of death [accident - 7.96 ± 2.26 mg GHB/L (n=8), suicide - 6.75 ± 3.22 mg GHB/L (n=7) and unknown/natural death - 5.14 ± 2.96 mg GHB/L (n=17), p0.05] and presence or absence of substances [absence - 6.37  2.61 mg GHB/L, presence - 6.96  3.38 mg GHB/L, p=0.405]. On the other hand, the results obtained suggest that the PMI (until 5 days between death and sampling) influences GHB whole blood concentration, noticed namely between 48 and 72 hours (24 - 48 hours (p=0.893), 48 - 72 hours (p<0.05); 72 - 96 hours (p=0.123). This study brings additional data regarding the usefulness of GHB levels in forensic toxicology, which might be further strengthened with larger, but comparable, studies from other laboratories and institutions in the forensic toxicology context.